Strengthening The Profile Of Pancasila Students (P5) And The Profile Of Rahmatan Lil Alamin Students (PPRA) Through The Implementation Of Local Wisdom Exhibition At Mts Al-Maarif 01 Singosari - Maulana, Sahrul; Rosyidah, Amiliya Nur; Azzahra, Fatimah; Fauziyah, Ulil (Proceeding of International Conference on Islamic Education (ICIED); Vol 9 No 1 (2024): Proceeding of International Conference on Islamic Education (ICIED), 2024)
This study aims to analyze the implementation of a local wisdom exhibition at MTs Al-Maarif 01 Singosari as a means to strengthen the Pancasila Student Profile (P5) and the Rahmatan Lil Alamin Student Profile (PPRA). The background of this research lies in the multidimensional challenges faced by education in Indonesia in shaping a young generation that excels not only intellectually but also possesses strong character aligned with the values of Pancasila and the teachings of Islam as rahmatan lil alamin . The implementation of the Pancasila Student Profile (P5) and the Rahmatan lil Alamin Student Profile (P2RA) programs in schools involves the principal, Civics and Social Studies teachers, and students as key elements. The principal acts as the leader, formulating policies and creating a supportive environment for both programs. Civics and Social Studies teachers serve as facilitators, integrating Pancasila values and the Rahmatan lil Alamin concept into the learning process, guiding students to understand and apply these values in their daily lives. Students, as the main participants, actively engage in these programs to internalize Pancasila values and become individuals who bring benefit to the world. This collaboration is expected to shape students' character, making them morally and socially outstanding individuals. The results of the study indicate that the local wisdom exhibition can be an effective medium for internalizing character values in students, strengthening national identity, and integrating Islamic teachings with local cultural contexts. This research is expected to contribute to the development of a character education model that is more relevant to the socio-cultural realities of students in Indonesia.